Assessing the value of cultural ecosystem services in urban landscapes: evidence from Tai’an City, China - Xu, Chongqing; Zhao, Teng; Shao, Yuting; Yan, Guihuan (Frontiers in Environmental Science, 2025)
Cultural ecosystem services (CES) refer to the intangible benefits provided by ecosystems to enhance the quality of human life. As cultural services are an important part of ecosystem services, how to account for the value of cultural ecosystem services CES has become an important research topic in the sustainable development of ecosystems. The establishment of a system of indicators and methodologies for cultural ecosystem services CES both improves comprehensive ecosystem assessments and facilitates scientific decision-making, and is essential for realizing synergies between ecological protection and economic and social development. Based on the existing accounting framework of cultural service value at home and abroad, this study constructs a more scientific and perfect indicator system of cultural service value, including four indicators: tourism and recuperation, leisure and recreation, landscape value-added and scientific research and education. research and education. Based on the four ecological and economic evaluation methods of travel costs act, time-cost method, market value approach and results-based approach, the cultural service value accounting model is optimized, and a new set of scientific research and education index value accounting model is established. Applying the indicator system and accounting model constructed in this paper study, the quantity of value of cultural services in Tai’an City in 2022 totaled 5.306 billion yuan CNY, which verified the feasibility of the indicator system and accounting model. Based on the accounting results, the study proposes a path to realize the value of cultural services in Tai’an. The results of this paper study can provide research references for the accounting and realization of ecological product value in different cities.